FACTORS INFLUENCING SUCCESS AND FAILURE IN MERGERS AND ACQUISITIONS : A Case Study of PT Unilever Indonesia Tbk - Surawan; Syamsurizal; Nurdin Ihsan; Khaidir; Dwi Firda; Indrayani; Muammar Khaddafi (PT. Radja Intercontinental Publishing, 2023)
Mergers and Acquisitions (M&A) are commonly used strategies by companies to achieve growth, expand market share, gain access to new technologies, and attain competitive advantage. However, the M&A process does not always go as planned and can face complex challenges. Many companies experience failures in executing mergers and acquisitions, which impact organizational performance and shareholder value. Therefore, it is crucial to understand the factors that influence success and failure in this process, particularly in the context of multinational companies like PT Unilever Indonesia Tbk. The literature suggests that there are numerous factors contributing to the success or failure of mergers and acquisitions. These factors include clear strategies and objectives, effective operational integration, organizational culture management, strong leadership, effective change management, human resource management, and external factors such as market conditions and regulations. It is important for companies to carefully consider and manage these factors in their merger and acquisition processes. The case study of PT Unilever Indonesia Tbk serves as the focus of this research article. The company has undergone several mergers and acquisitions in its history, including notable acquisitions like PT Rexona Indonesia and PT Annapurna. Therefore, analyzing the factors influencing success and failure in the mergers and acquisitions of PT Unilever Indonesia Tbk can provide valuable insights for other companies planning M&A in the future. This research adopts a qualitative approach by collecting data through relevant literature studies, financial reports, and company publications. The collected data is then systematically analyzed to identify the factors influencing the success and failure of mergers and acquisitions in PT Unilever Indonesia Tbk. The findings of this research are expected to provide better insights and understanding of the factors influencing success and failure in mergers and acquisitions, particularly in the context of PT Unilever Indonesia Tbk. With a better understanding of these factors, companies can take appropriate steps to enhance the chances of success in the M&A process.